Provision of liquidity through the primary credit facility during the financial crisis: a structural analysis - Erhan Artuç; Selva Demiralp (TÜSİAD-Koç University Economic Research Forum, 2009)
Over the course of the recent liquidity crisis, the Federal Reserve made several changes to its primary credit lending facility such as narrowing the spread between the primary credit rate and the target funds rate and increasing the term of the borrowing. In this paper, we use the model developed by Artuç and Demiralp (2008) to provide a structural assessment of the effectiveness of these changes. Our results suggest that these changes were effective in stabilizing the federal funds market.
Keywords: E40; E58; 330; Discount Window; Primary Credit; Federal Funds Market; Finanzmarktkrise; Kreditrationierung; Gesamtwirtschaftliche Liquidität; Öffentliche Anleihe; Kreditpolitik; USA